Pengaruh Media Peta Budaya Interaktif Berbasis Augmented Reality Terhadap Keterampilan Berpikir Kreatif pada Materi Keragaman Budaya Siswa Kelas IV SD - Ayu Mei Sinta Miranda; Ganes Gunansyah (Lembag, 2026)
The low creative thinking skills of students in learning Social Science (IPS) in elementary school, especially in the aspect of originality, is the background of this research. This research aims to find out the influence of Augmented Reality-based interactive cultural map media on the creative thinking skills of primary school grade IV students. This research uses a quantitative approach with a one group pretest-posttest design. The research subjects were 35 grade IV students at one of the elementary schools in Gresik who were selected with a saturated sampling technique. A research instrument in the form of a description test that measures creative thinking skills based on four aspects, namely fluency, flexibility, originality, and elaboration. Data analysis was carried out using the normality test and the paired t test. The research results show that there is an average increase in the student's creative thinking skills score from 9.31 in the pretest to 12.80 in the posttest. The t test results show a significant difference between before and after treatment. These findings show that Augmented Reality-based interactive cultural map media has a positive effect on students' creative thinking skills. The implication of this research is that Augmented Reality-based media can be used as an alternative to IPS learning innovation in elementary schools to improve students' creative thinking skills in 21st century learning.